2020
DOI: 10.1002/jaba.803
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transition to technician‐delivered telehealth ABA treatment during the COVID‐19 crisis: A preliminary analysis

Abstract: Telehealth delivery of applied behavior analysis treatment has focused on supervision or staff and parent training, rather than the direct delivery of treatment to clients. The novel coronavirus (COVID‐19) crisis had the potential to significantly disrupt access to direct treatment for individuals with autism. We report a sample of 17 cases that transitioned from in‐person to telehealth delivery of treatment when shelter‐in‐place orders were issued. Of these cases, 76% of participants transitioned to technicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 40 publications
6
52
1
2
Order By: Relevance
“…The current findings contribute to the recent literature on the use of telehealth to deliver behavior-analytic services (Crockett et al, 2020;Lerman et al, 2020;Pollard et al, 2021) and validate other recent research that telehealth can be an effective method of service delivery for some clients and staff (Barretto et al, 2006;Pellegrino & Di Gennaro Reed, 2020;Tomlinson et al, 2018;Wacker et al, 2013). The results demonstrate an objective and data-based process that can be used by behavior analysts and organizations to effectively transition to a new service modality, while attending to the important ethical guidelines and considerations outlined in recent publications (BACB, 2014;CASP, 2020a;CASP 2020b).…”
Section: Conclusion and Limitationssupporting
confidence: 64%
See 2 more Smart Citations
“…The current findings contribute to the recent literature on the use of telehealth to deliver behavior-analytic services (Crockett et al, 2020;Lerman et al, 2020;Pollard et al, 2021) and validate other recent research that telehealth can be an effective method of service delivery for some clients and staff (Barretto et al, 2006;Pellegrino & Di Gennaro Reed, 2020;Tomlinson et al, 2018;Wacker et al, 2013). The results demonstrate an objective and data-based process that can be used by behavior analysts and organizations to effectively transition to a new service modality, while attending to the important ethical guidelines and considerations outlined in recent publications (BACB, 2014;CASP, 2020a;CASP 2020b).…”
Section: Conclusion and Limitationssupporting
confidence: 64%
“…Many considerations were taken into account to evaluate the most ethical and likely effective service delivery model for each client. Recent publications have outlined specific guidelines for ethical decision-making around the delivery of behavior-analytic services through telehealth (Baumes et al 2020; Council for Autism Service Providers [CASP], 2020a, 2020b; Pollard et al 2021). It is critical to evaluate all potential variables that may affect treatment such as staff training and competency, client suitability and prerequisites for learning through telehealth, family interest, adequate equipment, access to a secure internet connection, family culture, environment, and safety.…”
Section: Adapting the Service Delivery Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies addressed specific pediatric populations including those diagnosed with eating disorders, 14,15,16,17,18 ADHD, 19 autism, 19,20,21,22,23 other severe mental health concerns, 24,25,26,27,28,29,30,31,32,33,34 and chronic medical conditions including epilepsy. 35,36 Among individuals with eating disorders, worsening symptoms (e.g., increased distress, binge eating) were reported, signaling the need for additional and/or sustained psychological care.…”
Section: Special Populationsmentioning
confidence: 99%
“…31 A small cohort of children with autism demonstrated symptom improvement while utilizing a virtual program led by providers and caregivers. 22 However, other studies of children with autism reported several challenges (e.g., decreased follow up, potential worsening of symptoms) during telehealth. 20,21 Other investigations of youth with complex disabilities reported increased mental health concerns among children and caregivers, 25 as well as mixed to low satisfaction with virtual care (e.g., decreased access to care, perceived as a poor fit for their child).…”
Section: Special Populationsmentioning
confidence: 99%